RECONCEPTUALIZING ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL AGE: A CRITICAL DISCOURSE ANALYSIS OF PRACTICES, KNOWLEDGE, AND POWER - Ahmad Nurozi; Moh Fatkur Rohman (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to reconceptualize Islamic Religious Education (IRE) in the digital age by examining the dynamics of practice, knowledge, and power through a Critical Discourse Analysis (CDA) approach. While prior studies largely emphasize pedagogical and technological aspects, this research addresses the lack of critical analysis on discourse and epistemological transformation. Using Fairclough’s three-dimensional model (text, discursive practice, and social practice), this qualitative study analyzes digital Islamic educational content, including social media and online learning platforms. The findings indicate that digitalization reshapes religious knowledge in several ways. At the textual level, Islamic discourse tends to simplify complex concepts, leading to ideological reduction. At the discursive level, knowledge production becomes decentralized but is influenced by algorithmic logic and platform dynamics. At the social level, religious authority shifts from institutional legitimacy to digital symbolic capital based on visibility and popularity. The study reveals an epistemological paradox: digital media democratizes access to knowledge while simultaneously increasing risks of distortion and weakening validation mechanisms. This research contributes theoretically by integrating CDA into Islamic education studies and highlights the need to strengthen critical digital literacy and adaptive validation frameworks in contemporary IRE. Keywords: Islamic Religious Education; Digitalization; Critical Discourse Analysis; Power/Knowledge; Epistemological Transformation.